A NEW SPECIES OF FREYCINETIA (PANDANACEAE) FROM PAPUA NEW GUINEA - KEIM, ARY PRIHARDHYANTO (REINWARDTIA, 2010)
KEIM, A.P. 2010. A new species of Freycinetia (Pandanaceae) from Papua New Guinea. Reinwardtia 13(2): 101-106.- Freycinetia streimannii A.P. Keim is newly described from Papua New Guinea. The novelty is closest to Freycinetia normanbyensis Huynh but is clearly separated by differences in the size of the cephalia and in the number of stigmas.